Completion Rate and Side-Effect Profile of Three-Month Isoniazid and Rifapentine Treatment for Latent Tuberculosis Infection in an Urban County Jail. (6th January 2016) - Juarez-Reyes, Maria; Gallivan, Mark; Chyorny, Alexander; O'Keeffe, Linda; Shah, Neha S.
Abstract: In an urban jail population, 3 months of isoniazid and rifapentine (3HP) was associated with an 85% latent tuberculosis infection treatment completion rate compared with 18% in a standard 9-month isoniazid treatment group. Among the 91 patients who started 3HP therapy, there were 2 treatment discontinuations from adverse drug reactions.